Rom, Italien: Marsfeld - von Hesberg, Henner (e-Forschungsberichte des DAI, 2023)
Working together with the Soprintendenza of Rome on the Campus Martius it has been possible to reconstruct the shape of the temple of Matidia, to clarify many details in the decoration of the theatre of Pompejus and to study some other buildings in their marble decoration. So, the connection of different parts of that important Region in Imperial Rome became more visible, mainly for the period of Domitian with his important feast of the Capitolia and further in the reign of Hadrian and the following emperors with their Dynastic cult.